ANALYSIS OF THE EFFECT OF INVESTMENT OPPORTUNITY SET AND PROFITABILITY ON FIRM VALUES WITH DIVIDEND POLICY AS INTERVENING VARIABLES IN MAIN SECTOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE IN 2015-2017 - Sinurat, Windo (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to analyse the set of investment and profitability opportunities that affect the value of the company with dividend policy as an intervening variable in the main sector companies listed in the Indonesian Stock Exchange in the 2015-2017 period. The population in this study amounted to 98 companies using the purposive sampling method obtained as many as 44 data. Data testing methods used are analysis of multiple linear regression and path analysis. The results of the first hypothesis study indicate that partially, the investment opportunity and profitability variable does not affect the dividend policy. In partial, the investment opportunity set variable does not have a significant effect on firm value, while the profitability variable has a significant positive effect on firm value. The investment policy variable is unable to act as an intervening variable between sets of investment opportunities on firm value. Dividend policy is also not able to play an intervening variable between profitability variables on firm value in the main sector companies listed on the Indonesia Stock Exchange in the period of 2015-2017.